Restructuring the Cellular Responses: Connecting Microbial Intervention With Ecological Fitness and Adaptiveness to the Maize (Zea mays L.) Grown in Saline–Sodic Soil - Singh, Shailendra; Singh, Udai B.; Trivdi, Mala; Malviya, Deepti; Sahu, Pramod K.; Roy, Manish; Sharma, Pawan K.; Singh, Harsh V.; Manna, M. C.; Saxena, Anil K. (Frontiers in Microbiology, 2021)
Salt stress hampers plant growth and development. It is now becoming one of the most important threats to agricultural productivity. Rhizosphere microorganisms play key roles in modulating cellular responses and enable plant tolerant to salt stress, but the detailed mechanisms of how this occurs need in-depth investigation. The present study elucidated that the microbe-mediated restructuring of the cellular responses leads to ecological fitness and adaptiveness to the maize (Zea mays L.) grown in saline–sodic soil. In the present study, effects of seed biopriming with B. safensis MF-01, B. altitudinis MF-15, and B. velezensis MF-08 singly and in consortium on different growth parameters were recorded. Soil biochemical and enzymatic analyses were performed. The activity and gene expression of High-Affinity K+ Transporter (ZmHKT-1), Sodium/Hydrogen exchanger 1 (zmNHX1), and antioxidant enzymes (ZmAPX1.2, ZmBADH-1, ZmCAT, ZmMPK5, ZmMPK7, and ZmCPK11) were studied. The expression of genes related to lateral root development (ZmHO-1, ZmGSL-1, and ZmGSL-3) and root architecture were also carried out. Seeds bioprimed with consortium of all three strains have been shown to confer increased seed germination (23.34–26.31%) and vigor indices (vigor index I: 38.71–53.68% and vigor index II: 74.11–82.43%) as compared to untreated control plant grown in saline–sodic soil at 30 days of sowing. Results indicated that plants treated with consortium of three strains induced early production of adventitious roots (tips: 4889.29, forks: 7951.57, and crossings: 2296.45) in maize compared to plants primed with single strains and untreated control (tips: 2019.25, forks: 3021.45, and crossings: 388.36), which was further confirmed by assessing the transcript level of ZmHO-1 (7.20 folds), ZmGSL-1 (4.50 folds), and ZmGSL-3 (12.00 folds) genes using the qPCR approach. The uptake and translocation of Na+, K+, and Ca2+ significantly varied in the plants treated with bioagents alone or in consortium. qRT-PCR analysis also revealed that the ZmHKT-1 and zmNHX1 expression levels varied significantly in the maize root upon inoculation and showed a 6- to 11-fold increase in the plants bioprimed with all the three strains in combination. Further, the activity and gene expression levels of antioxidant enzymes were significantly higher in the leaves of maize subjected seed biopriming with bioagents individually or in combination (3.50- to 12.00-fold). Our research indicated that ZmHKT-1 and zmNHX1 expression could effectively enhance salt tolerance by maintaining an optimal Na+/K+ balance and increasing the antioxidant activity that keeps reactive oxygen species at a low accumulation level. Interestingly, up-regulation of ZmHKT-1, NHX1, ZmHO-1, ZmGSL-1, and ZmGSL-3 and genes encoding antioxidants regulates the cellular responses that could effectively enhance the adaptiveness and ultimately leads to better plant growth and grain production in the maize crop grown in saline–sodic soil.